2015
DOI: 10.1111/eva.12280
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary biology and genetic techniques for insect control

Abstract: The requirement to develop new techniques for insect control that minimize negative environmental impacts has never been more pressing. Here we discuss population suppression and population replacement technologies. These include sterile insect technique, genetic elimination methods such as the release of insects carrying a dominant lethal (RIDL), and gene driving mechanisms offered by intracellular bacteria and homing endonucleases. We also review the potential of newer or underutilized methods such as reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 160 publications
(360 reference statements)
2
107
0
Order By: Relevance
“…The use of genome editing in environmental engineering has been discussed in the context of pest control, with new ways to eradicate agricultural pests (Huang et al 2016;Leftwich et al 2016), as well as that of disease eradication. For example, gene drive systems are being developed to eradicate malaria (Gantza et al 2015), and contemplated for the eradication of the Zika (Hegg 2016) arthropod vector.…”
Section: Discussionmentioning
confidence: 99%
“…The use of genome editing in environmental engineering has been discussed in the context of pest control, with new ways to eradicate agricultural pests (Huang et al 2016;Leftwich et al 2016), as well as that of disease eradication. For example, gene drive systems are being developed to eradicate malaria (Gantza et al 2015), and contemplated for the eradication of the Zika (Hegg 2016) arthropod vector.…”
Section: Discussionmentioning
confidence: 99%
“…This is a species-specific method of insect suppression in which insects are mass-reared under factory conditions, sterilized by irradiation, and then released (Leftwich et al, 2016). However, due to their adaptation to factory, laboratory, and irradiation, flies have significantly reduced fitness (Leftwich et al, 2016).…”
Section: Alternative Methods For Protection Against Olive Flymentioning
confidence: 99%
“…This is a species-specific method of insect suppression in which insects are mass-reared under factory conditions, sterilized by irradiation, and then released (Leftwich et al, 2016). However, due to their adaptation to factory, laboratory, and irradiation, flies have significantly reduced fitness (Leftwich et al, 2016). Zygouridis et al (2014) observed a substantial loss of variability between F1 and F2-F5 generations in the laboratory, while in F11 a complete adaptation to the new laboratory environment occurs.…”
Section: Alternative Methods For Protection Against Olive Flymentioning
confidence: 99%
“…; Servedio ; Wellenreuther and Sánchez‐Guillén ), host–parasite interactions (Leftwich et al. ; Myers and Cory ), evolutionary change accompanying invasion (Aktipis ; Gillespie ; Haig et al. ; Lee ; Olivieri et al.…”
Section: Revising Perceptions Of Women In Evolutionary Biologymentioning
confidence: 99%
“…Chapman and colleagues review efforts to improve biocontrol of insects, including work in her laboratory to use antagonistic seminal fluid proteins as a means of population control (Leftwich et al. ). From their decades of work on endemic plants, Olivieri et al.…”
Section: Revising Perceptions Of Women In Evolutionary Biologymentioning
confidence: 99%